Investigating flock-associated mimicry: examining the evidence for, and drivers of, plumage mimicry in the greater and lesser necklaced laughingthrush - Kamal Raj Gosai; Liping Zhou; Yang Liu; Edward L. Braun; Rebecca T. Kimball; Scott K. Robinson; Aiwu Jiang; Eben Goodale (Royal Society Open Science, 2024)
Visual mimicry is less understood in birds than in other taxa. The interspecific social dominance mimicry (ISDM) hypothesis asserts that subordinate species resemble dominant ones to reduce aggression. Plumage mimicry has also been consistently noted in mixed-species flocks (MSFs), suggesting a connection to grouping behaviour, although it is unclear whether this is linked to ISDM. We studied greater necklaced laughingthrush (GNLT, Pterorhinus pectoralis) and lesser necklaced laughingthrush (LNLT, Garrulax monileger), which were recently placed in different genera. Measurements of 162 museum specimens showed LNLT converging in sympatry with GNLT in necklace colour, but diverging in necklace to body ratio, with proportionally smaller necklaces. The species were closely associated in six of seven MSF systems from Nepal to China. In a study of foraging behaviour in Nepal, aggression was rare between the species, LNLT followed GNLT and had lower foraging rates when further from GNLT. Our data suggest a link between this MSF-associated mimicry and ISDM, and that the subordinate LNLT may be the mimic and gain more from the resemblance. The species spend much time together in dense and poorly lit vegetation, where the LNLTs resemblance to GNLTs potentially allows them to forage closer to GNLTs than would be otherwise possible.